Dying to Save Taxes: Evidence from Estate-Tax Returns on the Death Elasticity - Kopczuk, Wojciech; Slemrod, Joel (The Review of Economics and Statistics, 2003)
This paper examines data from U.S. federal tax returns to shed light on whether the timing of death is responsive to its tax consequences. We investigate the temporal pattern of deaths around the time of changes in the estate-tax system periods when living longer, or dying sooner, could significantly affect estate-tax liability. We find some evidence that there is a small death elasticity, although we cannot rule out that what we have uncovered is ex post doctoring of the reported date of death.